The Effectiveness of Peer Correction in Minimizing Grammatical Errors - Siti Ismahani; Nurul Hidayah Lubis; Widya Maharani; Rizki Tiara Ayunda; Huda Hizkia Ahmad Siregar (Lembaga Pengembangan Kinerja Dosen, 2024)
Grammatical accuracy remains a persistent challenge for learners in English as a Foreign Language (EFL) classrooms, particularly in academic writing contexts. Despite having adequate vocabulary and basic grammatical knowledge, many university students continue to produce recurring grammatical errors that weaken clarity and effectiveness in written communication. Traditional teacher-centered correction, although valuable, often fails to lead to sustained improvement, as students may not fully internalize the feedback provided. This study explores peer correction as an alternative and collaborative approach to minimizing grammatical errors in EFL academic descriptive writing. Peer correction encourages learners to actively engage with texts, negotiate meaning, and reflect critically on grammatical forms through interaction with classmates. By involving students in cycles of reviewing and revising each other’s work, this research aims to examine how peer correction influences learners’ grammatical awareness, accuracy, and confidence. Situated in a university EFL context, the study focuses on learners who are beyond beginner level but still experience persistent grammatical difficulties. The findings are expected to contribute to a deeper understanding of peer interaction as a pedagogical strategy that supports grammatical development, learner autonomy, and collaborative learning in academic writing classrooms.